2021
DOI: 10.1186/s12957-021-02308-0
|View full text |Cite
|
Sign up to set email alerts
|

Nephrectomy improves the survival of metastatic renal cell cancer patients with moderate to good performance status—results from a Finnish nation-wide population-based study from 2005 to 2010

Abstract: Background The purpose of this study was to evaluate the effects of cytoreductive nephrectomy (CN) and metastasectomies on the survival of patients with synchronous metastatic renal cell cancer (mRCC) using real-life, population-based national dataset. Methods Nationwide data, including all cases of synchronous mRCC in Finland diagnosed on a 6-year timeframe, based on the Finnish Cancer Registry and complemented with patient records from the treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…We assessed the risk of bias in 27 cohort studies using the ROBIN-1 tool. The overall risk of bias was determined to be moderate in 21 studies 10 , 18 20 , 22 35 , 39 42 and serious in six studies 17 , 21 , 36 38 , 41 . No study was found to be at critical risk of bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the risk of bias in 27 cohort studies using the ROBIN-1 tool. The overall risk of bias was determined to be moderate in 21 studies 10 , 18 20 , 22 35 , 39 42 and serious in six studies 17 , 21 , 36 38 , 41 . No study was found to be at critical risk of bias (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For metastatic CCRCC, there are currently two treatment options, including local therapies and systemic therapies. Local therapies include cytoreductive nephrectomy, metastasectomy, and stereotactic radiotherapy (SRT) (17)(18)(19). Systemic therapies include targeted therapy and immunotherapy (20,21).…”
Section: Discussionmentioning
confidence: 99%